Kepekaan Telur Spesific Pathogen Free dan Clean Egg Terhadap Virus Flu Burung (SENSITIVITY OF SPESIFIC PATHOGEN FREE EGGS AND CLEAN EGG TO THE AVIAN INFLUENZA VIRUSES SUBTYPE H5N1) - Kencana, Gusti Ayu Yuniati; Suartha, I Nyoman; Nurhandayani, Arini; Ramadhan, Muh (Jurnal Veteriner, 2014)
Avian Influenza which is  in Indonesia  known as Flu Burung  is caused by the avian influenza virussubtype H5N1 (AIV-H5N1). Vaccination is one of the major strategies for preventing and eradicatingAIV-H5N1 in Indonesia. Several factors can affect the potential vaccine such as viral content and mediaused for the propagation of the virus. One of the media commonly used to propagate  the virus is pathogenspecific free (SPF) embryonated chicken eggs. However, as the SPF eggs production is limited and expensive,the use of clean embryonated chicken eggs as an alternative need to examined. This study aimed todetermine the sensitivity of SPF and clean embryonated chicken eggs to the AIV-H5N1. The virus usedwas seed avian influenza virus (A/ Chicken/West Java (Subang)/29/2007)  which haa previously werepropagated  in SPF eggs and the Clean Eggs. The virus titer was determined as Embryo infective Dose 50%(EID50) using Reed and Muench method. Sensitivity of SPF eggs and Clean Egg to the VAI-H5N1 wascompared using  Chi-square statistical analysis. The titers of Avian Influenza Virus subtype H5N1 were106.83EID50/0.1ml in SPF eggs and 106.17EID50/0.1 ml in the Clean Eggs. Statistical analysis showed that,the sensitivity of SPF Eggs and Egg Clean  for the propagation of the VAI-H5N1 was not significantlydifferent.
Keywords: Avian influenza, sensitivity, SPF, Clean Egg,EID50